Rekomendasi Perbaikan Website Perpustakaan Dan Arsip Daerah Malang Menggunakan Pendekatan Human Centered Design (HCD) - Aldy Rakhman Kurniawan; Yusi Tyroni Mursityo; Hanifah Muslimah Az-Zahra (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
The library and archive website of Malang Region is one form of service from the Malang City Government especially under the responsibility of the Malang City Library and Archives Service. There is research on the Department of Library and Archives of the City of Malang, it is known that there are usability problems on the website they have, so that it affects the level of performance and services that are still below the user's expectations. The method used in this study is a Human Centered Design (HCD) approach that involves users at the stages carried out. HCD has the steps to be discussed, including understanding and specify context of usage, user requirement, design solutions, and design evaluation. The results of this study indicate that the prototype design with the application of the HCD approach has a better usability value than the current Malang Library and Archive website. In the aspect of effectiveness has increased, the website is currently categorized as normal while the prototype design is categorized as good. In the aspect of efficiency, the time needed to do the task has decreased time and the results of the questionnaire increased. So that the user does not need more resources to do the task. In the aspect of satisfaction has increased, the score obtained on the website today can be categorized as poor and unacceptable, while the score on the prototype can be categorized as excellent and can be accepted by the user.